Toxocara canis: A worldwide frequent zoonosrs - Rojas-Salamanca, Ana Carolina; León-Bustamante, María Camila; Bustamante-Saavedra, Olga Rocío (Universidad Pedagógica y Tecnológica de Colombia, 2016)
The toxocariasis is one of the most common zoonoses worldwide mainly caused by Toxocara canis, occurs most often in children associated with unfavorable conditions of hygiene, overcrowding, living with dogs parasitized, low socioeconomic status, bad geographic location and within environment in which animals deposit their feces, becoming a major source of contamination for humans. These parasites enter in the human beings accidentally, by direct contact or food contamination with dog feces.The parasite load is of vital importance as it is directly related to the severity of the disease, with different syndromes that occur and with the immune response discharged by the body, given the life cycle wich takes place within the human organism. This disease cannot be diagnosed by coproparasitological techniques, by which is required other methods such as the leukocyte with eosinophilia increase detection, also the ELISA proof and in some cases by biopsys.